2022
DOI: 10.3389/fneur.2022.926436
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and risk factors of complications after cranioplasty with polyetheretherketone and titanium mesh: A single-center retrospective study

Abstract: BackgroundTo compare the incidence of complications and constructive effects of cranioplasty with polyetheretherketone (PEEK) and titanium mesh after decompressive craniectomy, and to further explore potential risk factors of postoperative and post-discharge complications.MethodsA retrospective study was conducted on 211 patients who underwent PEEK or titanium mesh cranioplasty in the Department of Neurosurgery of Zhujiang Hospital, Southern Medical University, between July 2017 and September 2021. Demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Only 1 article achieved level 1. The quality of evidence concerning the specific questionnaire and scores are presented in Supplemental Table 2, [10][11][12][13][14][15][16][17][18][19][20][21][22] Supplemental Digital Content 2, http://links.lww. com/SCS/G319.…”
Section: Resultsmentioning
confidence: 99%
“…Only 1 article achieved level 1. The quality of evidence concerning the specific questionnaire and scores are presented in Supplemental Table 2, [10][11][12][13][14][15][16][17][18][19][20][21][22] Supplemental Digital Content 2, http://links.lww. com/SCS/G319.…”
Section: Resultsmentioning
confidence: 99%
“…1,9,12,17,25 Several studies have reported superior outcomes in PEEK implants when compared to autologous and other alloplastic materials. 1,2,4,6,7,18,[22][23][24][26][27][28] Sharma et al 17 compared dimensions of digital CT-modeled PEEK implants versus their printed counterparts and found significant reliability and accuracy between them. In another study, Wandell et al 9 reported high intraoperative accuracy between the defect and the implant fit.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the use of computer-designed patient-specific PEEK implants has increased in popularity due to their high accuracy, decreased intra-operative time (155 versus 264 min in autologous), 24 shaping, and decreased insetting efforts 1,9,12,17,25 . Several studies have reported superior outcomes in PEEK implants when compared to autologous and other alloplastic materials 1,2,4,6,7,18,22–24,26–28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors influencing this phenomenon include not only the material but also the design, mechanical loading, and notably, the interface between the implant and the periosteum. Titanium implants, while studies comparing different materials for craniofacial reconstruction are still limited, appear to be associated with increased donor site comorbidity, including bone resorption [35]. Countless studies have demonstrated that implants crafted from specific materials, such as titanium alloys, may induce peri-implant bone resorption attributable to stress shielding phenomena [36,37].…”
Section: Prostheses Can Lead To Underlying Bone Resorptionmentioning
confidence: 99%